Speech text of international conference on sustainable development for community empowerment (unitE 2023) / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
I am pleased to join you today at the virtual International Conference on Sustainable Development for Community Empowerment or unitE 2023, organised by the Community Network Centre (CNC), Office of Industry, Community and Alumni Network (ICAN), Universiti Teknologi MARA.